Status Hak Waris Perkawinan Beda Agama di Indonesia Perspektif Yuris Islam Klasik Dan Kontemporer - Tohari, Ilham; Hazyimara, Karunia (Pustaka Peradaban, 2023)
This research aims to investigate the inheritance status of interfaith marriages in Indonesia's multicultural basis according to classical and contemporary jurisprudence. The method used is library research with a descriptive-qualitative approach. The results of the research are that multicultural-based fiqh can be understood through the reinterpretation of religious texts using the maqashid sharia approach. Interfaith marriage as one of the effects of social interaction in a multicultural country still leads to a taboo understanding that interreligious marriage in Indonesia is not allowed, as classical and contemporary jurist opinion generally forbids it. Questioning the status of inheritance in interfaith marriages, the scholars of the four schools of thought, Ali as-Shabuni, Sayyid Sabiq, Muhammad as-Syaukani, and Mustafa as-Salabi agreed that their inheritance rights were hindered, while according to the Imami school of thought, Ibn Taimiyah and Ibn Qayyim al-Jauzi and Yusuf Al- Qardhawi was not deterred by the pretext of helping each other. In Indonesia, the inheritance rights of interfaith marriages are discussed in the decision of the Supreme Court (MA) No. 368K/AG/1995 and the decision of the Supreme Court of the Republic of Indonesia Number 51K/AG/1999 which shows that in terms of not obtaining inheritance rights, they will receive a